2018
DOI: 10.14739/2310-1210.2018.6.146780
|View full text |Cite
|
Sign up to set email alerts
|

8-isoprostane as the main marker of oxidative stress

Abstract: Цель работы-обобщение данных экспериментальных и клинических исследований, которыми установлено, что в основе ведущих метаболических процессов человека лежат окислительно-восстановительные реакции. Среди них особую роль играют свободнорадикальные реакции, ведущие к образованию перекисных соединений. Таким образом, актуально определение параметров оксидативного стресса, его интенсивности, необходимой для адекватной оценки компенсаторных возможностей организма, прогноза течения заболевания и эффективности лечени… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…6,[35][36][37] The levels of 8-isoprostane are known to increase in response to oxidative stress. 38 Hence, 8-Isoprostane, which is considered as the most stable biomarker of oxidative stress was assessed in the serum of the participants enrolled in the study. 39 In the present study, participants with increased body weight and at a risk of metabolic syndrome showed a trend of increasing oxidative stress over next eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…6,[35][36][37] The levels of 8-isoprostane are known to increase in response to oxidative stress. 38 Hence, 8-Isoprostane, which is considered as the most stable biomarker of oxidative stress was assessed in the serum of the participants enrolled in the study. 39 In the present study, participants with increased body weight and at a risk of metabolic syndrome showed a trend of increasing oxidative stress over next eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically stable isoprostane detected in plasma and urine is a dependable biomarker for peroxidation induced through free radicals. 41 Research evidence suggests that it is a promising index for inflammatory disorders promoted by cyclooxygenase. 42,43 The researcher found lower in urinary 8-iso-PGF 2α content in RA patients than that of a normal individual, which was significant.…”
Section: -Isoprostanementioning
confidence: 99%
“…Oxidative stress occurs due to the increased formation of free oxygen radicals and/or weakened functioning of the antioxidant barrier [ 3 ]. An uncontrolled release of free radicals and their derivatives by damaging nucleic acids, enzymes, and biological membranes leads to the development of pathological conditions [ 5 ]. Oxygen free radicals are responsible for lipid peroxidation (LPO) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%